The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10528-010-9393-5
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-Based Case–Control Study of the Human CYP11B2 Gene and Essential Hypertension in Yi and Hani Minorities of China

Abstract: This haplotype-based case-control study investigated whether the aldosterone synthase gene (CYP11B2) might be implicated in the pathogenesis of essential hypertension in Yi (226 individuals) and Hani (296 individuals) minorities of China. Four tag SNPs (rs4536, rs4545, rs3097, and rs3802230) and the K173R polymorphism were genotyped using the PCR-RFLP method. In the Hani minority, rs4536 was significantly associated with hypertension, after Bonferroni correction. H9 AGGC constructed by tag SNPs was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The combined P =  0.001, OR = 1.20, 95% CI = 1.08–1.34, I 2  = 0.0% ( P =  0.39), which means no heterogeneity existed between two studies, and the C allele of rs3802230 might be a risk factor for essential hypertension in the Han Chinese population. Chen et al also analyzed these SNPs in Yi and Hani Minorities of China, and found rs4536 was significantly associated with hypertension in the Hani minority, however, no association was found in the Yi minority [32].…”
Section: Discussionmentioning
confidence: 99%
“…The combined P =  0.001, OR = 1.20, 95% CI = 1.08–1.34, I 2  = 0.0% ( P =  0.39), which means no heterogeneity existed between two studies, and the C allele of rs3802230 might be a risk factor for essential hypertension in the Han Chinese population. Chen et al also analyzed these SNPs in Yi and Hani Minorities of China, and found rs4536 was significantly associated with hypertension in the Hani minority, however, no association was found in the Yi minority [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they tend to not migrate or not intermarry with other minorities. 8,9 Thus, the genetic backgrounds of samples in this study were very similar and the BP phenotypes were not affected by drugs. The above features raise the power of our evaluation of the contributions of genetic factors to EH and make our study findings much more objective.…”
Section: Discussionmentioning
confidence: 72%
“…The above conditions minimize the influence of confounding environmental factors and reduce genetic diversity in founder populations. 8,9 A genetic association study based on such an isolated population could increase the chances of identifying genetic factors contributing to EH. We recruited hypertensive and normal individuals from the Yi minority population in this study, and attempted to explore the association of the prolylcarboxypeptidase (PRCP) gene with EH.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hani ethnic minority has the low frequency of migration and intermarriage with other minorities. 7,8 This reduced genetic diversity in founder populations could increase the genetic study power to explore the susceptible gene markers for EH.…”
Section: Introductionmentioning
confidence: 99%